INOVASI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM (PAI) DENGAN MEMANFAATKAN PLATFORM WORDWALL DI SMP MA'ARIF 4 PAMEKASAN - Zainol Hasan; Halimatus Sa'diyah; Emna Laisa (Cognitive: Jurnal Pendidikan dan Pembelajaran, 2025)
long with the development of technology, teachers are required to be able to adapt to the use of technology to improve the quality of education. There are many platforms that can be used as media in the learning process, one of which is easy to use is wordwall. Wordwall platforms can be an option to deliver interactive material. There are a lot of designs that can be chosen and even teachers can also design teaching materials themselves according to their desires. Even teachers can develop audio-visual-based teaching materials using the Canva application. This research is a research and development that aims to produce products in the form of technology-based PAI learning media. The results of this study show the effectiveness of using technology-based PAI learning media using Canva.